Escape of poetry from the village to the city in interwar Lithuania - Kilinskaitė, Emilija (Vilnius University Open Series, 2021)
The article examines the thematic transformation of interwar Lithuanian poetry from the countryside to the city in 1918-1940. Based on images and lyrical experiences in interwar Lithuanian poetry, it reviews the changing features of the urban poetry of the time, discusses the city as it is revealed in it; the changing perception of oneself as an individual in the society of the time, the changes in one's environment and community in the face of urbanisation. During the two decades of independent Lithuania, the tension between countryside and urban poetry has come almost full circle: at the beginning of the period, we experience the natural "invasion" of the city into poetry; at the end of the period, the city becomes a commonplace, and the reminiscences of countryside adopt nostalgic feeling.
Keywords: poetry; urbanization; interwar; Lithuania